The Effects of Polymer–Nitrogen Fertilizer on Biomes in Drip-Irrigated Wheat Soil - Yan Sun; Chunying Wei; Shenglin Zhang; Hua Fan; Dashuang Hong; Hong Huang; Kaiyong Wang (Microorganisms)
Polymer application combined with nitrogen (N) fertilization can increase soil N transformation efficiency. However, the mechanism of polymer influencing soil biocommunity characteristics and nitrogen transformation is still unclear. In this field experiment, a self-developed water-soluble polymer material (PPM, a mixture of anionic polyacrylamide, polyvinyl alcohol, and manganese sulfate) was combined with N fertilization N100 (300 kg/hm2 of N), PN100 (PPM + 300 kg/hm2 of N), and PN80 (PPM + 240 kg/hm2 of N) to investigate soil biodiversity, enzyme activities, and metabolomics. The results showed that under the application of PPM, the contents of soil total nitrogen (TN), alkali hydrolyzable nitrogen (ANS), nitrate nitrogen, organic carbon (SOC), and microbial biomass nitrogen (MBN) increased with a decrease in the N application rate, while soil bulk density, pH, and EC (electrical conductivity) decreased. The Chao 1 index of soil bacterial and nematode communities of the PN80 treatment was 30.6% and 10.7% higher than that of the N100 treatment, respectively, and the Shannon index was 2.72% and 2.64% higher than that of the N100 treatment, respectively. In the short term, the application of PPM affected the structure and composition of soil bacterial and nematode communities. In particular, the relative abundances of omnivorous (Aporcelaimellus) and bacterivorous (Prismatolaimus) nematodes were significantly higher than those of the N100 treatment. These changes further regulated the soil metabolites, promoting soil nitrogen transformation. This study will provide a scientific basis for nitrogen reduction in drip-irrigated wheat planting in arid regions.